Direct kidney injury or lower extremity ischemia induced indirect kidney injury: Which one is more harmful for kidneys?. (June 2021) - Eygi, Bortecin; Gokalp, Orhan; Kiray, Muge; Iscan, Sahin; Gokalp, Gamze; Demirbas, Bahar; Yesilkaya, Nihan; Iner, Hasan; Gür, Mehmet S; Besir, Yuksel; Yilik, Levent; Gurbuz, Ali
Objectives: The aim of this study was to investigate and compare the severity of kidney damage following lower limb ischemia–reperfusion and direct kidney ischemia–reperfusion. Methods: Thirty Sprague Dawley male rats were randomly divided into three groups; lower extremity ischemia–reperfusion group (Group 2), renal ischemia–reperfusion group (Group 3) and control (anesthesia and median laparotomy only) (Group 1). In group 3, 1-h ischemia was performed on the kidney and in group 2, 1-h ischemia was performed on the left lower extremity. This procedure was followed by reperfusion for 24 h. Renal tissues were removed after the reperfusion period and the groups were evaluated for glutathioneperoxidase activity, malondialdehyde and GSH levels, and furthermore, their histolopathological scores were calculated. Results: Renal malondialdehyde levels were significantly higher in Group 2 and Group 3 than they were in the Control group. There was no significant difference in renal malondialdehyde levels between Group 2 and Group 3. Kidney glutathione (GSH) levels were statistically lower in Group 2 and Group 3 than in the Control group. No statistically significant difference was found between Group 2 and Group 3 regarding their GSH levels. In histological evaluation, there was no statistically significant difference between Group 2 and Group 3 in terms of kidney damage score. Conclusions: This study has identified that lower extremity ischemia induces remote kidney damage with similar features to kidney injury, occurring after direct kidney ischemia–reperfusion.